Modeling of mechanical interaction between filler particles and binder in polymer-silicate nanocomposites under finite macrodeformation - Garishin, Oleg Konstantinovich; Korlyakov, Anton Sergeevich (Computational Continuum Mechanics, 2009)
Theoretical investigation of the stress state of polyolefin/clay nanocomposites at structural level is carried out taking into account the orientation of filler particles under external loading conditions. Stacks of parallel ultra-thin silicate nanoplates (tactoids) are considered as the filler. It is demonstrated that the mechanical properties of such inclusions depend on the material in the interlayer spaces. If the spaces are filled with a soft material like a mixture of polymeric compound and water adsorbed by clay, the tactoids will be more flexible nanoplates than those whose interlayer spaces contain the material similar to that in the matrix. The case when filler particles are oriented in the direction of external load is optimal from the point of view of minimization of inclusion bending, which may cause their fracture. Estimation of the effective module of nanocomposites with consideration of the filler concentration and the properties of the material between the tactoid nanoplates is made using the solutions obtained in this study. It is shown that the filler concentration in this case affects the macro-module increment more strongly than in the case of conventional particulate composites.
Keywords: polyolefin polymers; layered silicate nanofiller; tactoid; structure; stresses; strains; elastic macro-modulus